2021
DOI: 10.3390/antibiotics10070846
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Profile of Pseudomonas aeruginosa Canine Isolates from a Multicentric Study in Romania

Abstract: Treating infections caused by Pseudomonas aeruginosa is increasingly difficult due to high antibiotic resistance, materialized through the presence of multiple resistance strains, as well as due to rapid development of resistance throughout treatment. The present survey was conducted to investigate the antibiotic susceptibility profile of Pseudomonas aeruginosa pathogens in two University Veterinary hospitals from different geographical regions of Romania (i.e., Southwest Timișoara county and Northeast Iași co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
(50 reference statements)
1
19
1
Order By: Relevance
“…P. aeruginosa possesses a naturally-occurring AmpC β-lactamase that is not inhibited by the currently available lactam inhibitors, clavulanic acid, sulbactam, and tazobactam, and therefore confers resistance to antibiotic combinations [ 87 , 88 ]. Several earlier studies have reported high proportions of P. aeruginosa resistance to ceftazidime and aztreonam [ 84 , 89 , 90 , 91 ]. This is consistent with the 39% resistance observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa possesses a naturally-occurring AmpC β-lactamase that is not inhibited by the currently available lactam inhibitors, clavulanic acid, sulbactam, and tazobactam, and therefore confers resistance to antibiotic combinations [ 87 , 88 ]. Several earlier studies have reported high proportions of P. aeruginosa resistance to ceftazidime and aztreonam [ 84 , 89 , 90 , 91 ]. This is consistent with the 39% resistance observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this concerning record, there is limited information on the prevalence of AMR in bacterial populations from humans [ 18 , 19 , 20 , 21 ] and, with the exception of a few studies on the prevalence of Staphylococcus spp. in dogs [ 22 , 23 , 24 ], AMR data in companion animals is lacking. In this study, we found that 44.11% of healthy dogs from households carried ESC-R Enterobacterales , which is similar to carriage rates of cefotaxime-resistant E. coli isolates found in healthy dogs in the Netherlands (45%) [ 14 ], and slightly lower than that reported in dogs from South Korea (49%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low susceptibility of the isolates to anti-pseudomonal antibiotics, such as aztreonam, imipenem, ceftazidime, cefepime, and piperacillin associated with tazobactam, is alarming. It reflects the skillful defense developed by P. aeruginosa against these agents and the scarce remaining therapeutic resources [ 36 , 37 ]. Another valuable finding was the greater susceptibility of the isolates to ceftazidime ( Table-1 ) than to cefepime, as the latter is a fourth-generation cephalosporin.…”
Section: Discussionmentioning
confidence: 99%